ХОЁР ТАНХИМТАЙ ПАРЛАМЕНТЫН АНГИЛАЛ, ХЭВ МАЯГ, ЗАГВАРУУД - Д.Сүхболд (Politology, 2023)
here are shown main criterions of political researchers and scientists about the classification or styles of bicameral parliamentary system; About key bicameral parliamentary models around the world, such as Aristocratic, Federal and discussioned.